Contamination of chicken carcasses and the abattoir environment with Listeria monocytogenes in Taiwan. Issue 5 (3rd September 2021) - Lin, C.-H.; Adams, P. J.; Huang, J.-F.; Sun, Y.-F.; Lin, J.-H.; Robertson, I. D.
ABSTRACT: 1. The following study provides the first data on the detection and types of Listeria monocytogenes isolated from broiler chickens during processing and from six Taiwanese abattoir environments. 2. Listeria monocytogenes was not detected in any cloacal (n = 120) or environmental (n = 256) samples collected before and during processing, indicating that faecal material and the environment of abattoirs were not important sources of L. monocytogenes for poultry carcases. However, 28 of 246 (11.4%; 95% CI: 7.7–16.0) rinse samples collected from carcases post-evisceration from three abattoirs were positive for L. monocytogenes . 3. The only serotypes detected were 1/2a (82.1%; 95% CI: 63.1–93.9) and 1/2b (14.3%; 95% CI: 4.0–32.7), with 3.6% (95% CI: 0.1–18.3) non-typable isolates. 4. Characterisation by Pulsed Field Gel Electrophoresis (PFGE) identified five PFGE types, confirming cross-contamination with L. monocytogenes during evisceration, chilling and post-chilling. 5. These findings highlight the potential for cross-contamination to occur through direct contact between carcases, especially whilst in chilling tanks.